Development of Integrated Science Teaching Materials of Al-Quran Verses in Improving Students' Religious Attitudes in Madrasas - Abdul Kadir; Muhammad Shaleh Assingkily; Jahidin; Sufiani; Salma Samputri; Mustapa Ahmad (Nazhruna: Jurnal Pendidikan Islam, 2024)
Various previous studies have responded to the study of the challenges of moral degradation in the digital era. However, the focus of the study has not yet been found in the form of the integrality of Qur'anic verse-based Learning with a locus in Madrasah Tsanawiyah. It is believed that this integrality fosters students' religious attitudes. This study aims to develop a product of integrated science teaching materials of the Qur'anic verses to improve students' religious attitudes in madrasah. This type of research is research and development (R&D), adapting the Borg & Gall model with the ADDIE stages, analysis, design, development, implementation, and evaluation, because it is considered relevant to describe the chronology of Learning product development from the beginning. The results of this study found that science teaching materials integrated with al-Qur'an verses are valid and very feasible to use in student science Learning at MTsN Konawe Regency with an average value of 91.98% of the validity test results. Then, science teaching materials integrated with al-Qur'an values have a practicality value to be applied at MTsN Konawe Regency, marked by the average score of 1.64 small groups and 1.79 large groups. Science teaching materials integrated with al-Qur'an values are effectively used in science Learning after being developed in small and large groups with a probability value (r) Sig. = 0.000 <a = 0.05, meaning there is a significant difference in students' spiritual attitudes before and after treatment using science teaching materials integrated with the Qur'an. Thus, it is concluded that the product of science teaching materials integrated with al-Qur'an verses is appropriate for improving students' religious attitudes in madrasah.